Analysis of Mustahik's Welfare through The Distribution of Zakat Funds in "The Ciamis Care Program" at Baznas, Ciamis District - Muplihin, Fahrul Zainal; Mujib, Haqibul; Aristhantia, Isti Tresna; Nurliani, Rika (Syari'ah Economics, 2023)
The purpose of this study is to determine the mechanism of distribution of zakat funds and efforts to improve the welfare of the community in the Ciamis Peduli program on rutilahu assistance in Baznas Ciamis Regency, if viewed from the theory of social welfare. This research uses descriptive qualitative methods with data collection techniques of observation, interviews and documentation. Taking informants on aid recipients at Baznas Ciamis Regency. The result of this research is that the distribution mechanism is that Baznas first conducts socialization and then cooperates with the village, then the village provides the assistance in the form of building materials and after completion the village gives a report on the results of the distribution of assistance to Baznas. Then the efforts made have an effect on the welfare of Mustahik, especially the recipients of assistance where the recipients of the Ciamis Peduli program assistance, especially assistance for uninhabitable houses.